2022
DOI: 10.2196/33818
|View full text |Cite
|
Sign up to set email alerts
|

A Stress and Pain Self-management mHealth App for Adult Outpatients With Sickle Cell Disease: Protocol for a Randomized Controlled Study

Abstract: Background This paper describes the research protocol for a randomized controlled trial of a self-management intervention for adults diagnosed with sickle cell disease (SCD). People living with SCD experience lifelong recurrent episodes of acute and chronic pain, which are exacerbated by stress. Objective This study aims to decrease stress and improve SCD pain control with reduced opioid use through an intervention with self-management relaxation exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Pediatric SCA patient education can: improve knowledge, decrease hospitalization, improve medication possession ratio, lead to better SCA-related functioning, and lower pain impact [5][6][7][8][9][10]. Helpful resources currently available include self-care toolkits and apps that are easily accessible to academics but are not readily available to youth following internet searches [11][12][13]. Breakey et al demonstrated by mimicking internet searches of adolescents that there is a lack of information with features desirable to adolescents on the internet written at an appropriate reading level [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric SCA patient education can: improve knowledge, decrease hospitalization, improve medication possession ratio, lead to better SCA-related functioning, and lower pain impact [5][6][7][8][9][10]. Helpful resources currently available include self-care toolkits and apps that are easily accessible to academics but are not readily available to youth following internet searches [11][12][13]. Breakey et al demonstrated by mimicking internet searches of adolescents that there is a lack of information with features desirable to adolescents on the internet written at an appropriate reading level [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric SCA patient education can: improve knowledge, decrease hospitalization, improve medication possession ratio, lead to better SCA‐related functioning, and lower pain impact [5–10]. Helpful resources currently available include self‐care toolkits and apps that are easily accessible to academics but are not readily available to youth following internet searches [11–13]. Breakey et al.…”
Section: Introductionmentioning
confidence: 99%